FRI0136 Ovarian reserve, as assessed by measuring serum anti-mÜllerian hormone levels, declines more rapidly over time in rheumatoid arthritis patients compared to controls. (15th June 2017) - Brouwer, J; Laven, JS; Hazes, JM; Erler, NS; Visser, JA; Dolhain, RJ
Abstract : Background: The ovarian reserve in women with rheumatoid arthritis (RA) may be compromised, based on a reduced fertility 1 and a younger age at menopause 2 . Serum anti-Müllerian hormone (AMH) levels are a proxy for the ovarian follicle pool, and are the most reliable predictor of the age at which menopause sets in. Objectives: Our objectives were to study the intra-individual change in AMH levels in female RA patients, and to study the effect of RA-related factors on the decline of AMH levels over time. Methods: Female RA patients from a nationwide prospective cohort study (PARA study) in 2002–2008, were re-assessed in 2015–2016. Serum AMH levels were measured using the pico AMH assay (provided by Ansh Labs, Texas, USA) and compared to healthy controls (Lie Fong, 2012) 3 . A linear mixed model was built to assess the effect of RA-related clinical factors on the decline of serum AMH levels over time. Results: 128 women were re-assessed at a mean age of 42.6±4.4 years, with a median disease duration of 15.8 (IQR 12.7–21.5) years. The participants appeared a more fertile selection of the original PARA cohort. The mean time between the first and the follow-up assessments was 10.7±1.8 years. At follow-up, more patients had AMH levels below the 10th percentile of controls (39%; 95% CI 31 – 48%), than at baseline (16%; 95% CI 9.3–22%). The linear mixed model showed only a significant effect of age, and no significant effect of RA-related factors on the decline of serum AMH levels over time. Conclusions: This is the first longitudinal study on AMH levels in women with RA, and is showing that AMH levels in RA patients decline more rapidly over time compared to healthy controls. This indicates that the disease process of RA has a negative impact on the ovarian reserve of young pre-menopausal RA women. References: Brouwer J, Hazes JM, Laven JS, Dolhain RJ. Fertility in women with rheumatoid arthritis: influence of disease activity and medication. Ann Rheum Dis 2015;74:1836–41. Del Junco D. The relationship between rheumatoid arthritis and reproductive function [Dissertation]. Houston, Texas: The University of Texas Health Sciences Center at Houston School of Public Health; 1988. Lie Fong S, Visser JA, Welt CK, et al. Serum anti-mullerian hormone levels in healthy females: a nomogram ranging from infancy to adulthood. J Clin Endocrinol Metab 2012;97:4650–5. Acknowledgements: This study was funded by the Dutch Arthritis Foundation (Reumafonds). The pico AMH assays were generously provided by Ansh Labs (Houston, Texas, USA). Furthermore, we would like to thank all patients and rheumatologists who contributed to the PARA study, as well as all researchers and laboratory workers who have worked on this project. Disclosure of Interest: J. Brouwer: None declared, J. Laven: None declared, J. Hazes: None declared, N. Erler: None declared, J. Visser: None declared, R. Dolhain Grant/research support from: unrestricted research grant by UCB Pharma BV